EFEK EDUKASI “PAKET HARMONIS” TERHADAP PENGELOLAAN DIRI PEREMPUAN MENOPAUSE DALAM MENGATASI PERUBAHAN MASA MENOPOUSE - Marini Agustin; Irna Nursanti (Akademika : Jurnal Teknologi Pendidikan, 2020)
Menopause is a phase that will be experienced by every woman who usually occurs above the age of 40 years. Women are said to be menopausal if their menstrual cycles have stopped for 1 year. The purpose of this study was to determine the effect of Harmonious Packages on the self-management of menopausal women in overcoming changes in menopause in Bogor City. This research is a quantitative study with a quasi-experimental method using a pre-post test with control approach. Data collection is done quantitatively. Large sample of 60 respondents, consisting of 30 intervention groups and 30 control groups, which were taken by purposive sampling technique.The results of bivariate analysis on self-management (self-monitoring, self-control, self-esteem) obtained P Value = 0.0000 (P Value <α = 0.005), these results prove that the